2022
DOI: 10.1186/s12882-022-02853-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an online patient decision aid for kidney failure treatment modality decisions

Abstract: Background Patient decision aids (PtDAs) support patients and clinicians in shared decision-making (SDM). Real-world outcome information may improve patients’ risk perception, and help patients make decisions congruent with their expectations and values. Our aim was to develop an online PtDA to support kidney failure treatment modality decision-making, that: 1) provides patients with real-world outcome information, and 2) facilitates SDM in clinical practice. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“… 45 , 46 , 47 Because of the simplicity of the KFRE and accessibility of the variables included in the KFRE, it has previously been implemented into EMR systems to support both clinical practice and research on CDS tool integration. 38 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 Via its integration with EMR systems, KFRE can be automatically calculated, improving the identification of patients at risk of developing kidney failure and improving provider workflow. 45 , 46 , 47 , 49 , 52 , 53 , 55 , 57 , 60 , 61 Others 45 , 47 have suggested that incorporating automatic prompts into a KFRE CDS tool to encourage providers to order urinary albumin-to-creatinine ratio testing, which is not routinely collected, would improve the accuracy of KFRE and downstream patient outcomes.…”
Section: History Of Emrsmentioning
confidence: 99%
“… 45 , 46 , 47 Because of the simplicity of the KFRE and accessibility of the variables included in the KFRE, it has previously been implemented into EMR systems to support both clinical practice and research on CDS tool integration. 38 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 Via its integration with EMR systems, KFRE can be automatically calculated, improving the identification of patients at risk of developing kidney failure and improving provider workflow. 45 , 46 , 47 , 49 , 52 , 53 , 55 , 57 , 60 , 61 Others 45 , 47 have suggested that incorporating automatic prompts into a KFRE CDS tool to encourage providers to order urinary albumin-to-creatinine ratio testing, which is not routinely collected, would improve the accuracy of KFRE and downstream patient outcomes.…”
Section: History Of Emrsmentioning
confidence: 99%
“…the ‘Multiple Stakeholder Reasoning—Shared Understanding’ approach [ 113–117 , 126–129 ]. The evidence from those evaluated indicates that integrating PtDAs within kidney pathways supports PwKF to make informed, value-based treatment decisions about dialysis and shared decisions with their family and kidney practitioners [ 2 , 74 , 137–144 , 149 , 151 , 152 , 154–157 ].…”
Section: Why Patient Decision Aids Enable Kidney Services To Support ...mentioning
confidence: 99%